2014
DOI: 10.1161/strokeaha.114.005781
|View full text |Cite
|
Sign up to set email alerts
|

A Dark Side of Subcortical Diffusion-Weighted Lesions?

Abstract: Background and Purpose— Diffusion-weighted imaging (DWI) is highly accurate in identifying and locating ischemic stroke injury. Few studies using DWI have investigated large subcortical infarctions (LSIs). We aimed to study clinical characteristics, cause, and outcome in patients with ischemic stroke with LSI diagnosed on DWI and compare these with those who had lacunar DWI lesions or DWI lesions located elsewhere. Methods— Patients with stroke admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The groups of patients depended on the following:

Group I, location of DWI lesions: DWI lesions were categorized into the following pre-defined subgroups: cortical lesions, confined to the supratentorial cortex; large subcortical lesions, located in the hemispheric white matter, basal ganglia, internal capsule, thalamus or corona radiata with a diameter ≥15 mm; lacunar lesions, located in the same territory as large subcortical lesions with a diameter <15 mm; mixed cortical–subcortical lesions, located in both supratentorial cortex and subcortex; cerebellar lesions, confined to the cerebellum; brainstem lesions, confined to the brain stem and multiple lesions, lesions located in more than one of the above defined areas. This predefined protocol of DWI location has been utilized in prior studies 16,17

Group II, time window: patients were categorized into two different subgroups depending on whether they were admitted within or after 6 h of stroke onset.

Group III, persisting major occlusion or no occlusion: patients were categorized into two different subgroups according to the presence of total proximal middle cerebral artery (MCA) occlusion or no occlusion of any cerebral vessel on MRA at 24 h. Total occlusion of intracranial arteries was defined as 100% occlusion on MRA.

…”
Section: Methodsmentioning
confidence: 99%
“…The groups of patients depended on the following:

Group I, location of DWI lesions: DWI lesions were categorized into the following pre-defined subgroups: cortical lesions, confined to the supratentorial cortex; large subcortical lesions, located in the hemispheric white matter, basal ganglia, internal capsule, thalamus or corona radiata with a diameter ≥15 mm; lacunar lesions, located in the same territory as large subcortical lesions with a diameter <15 mm; mixed cortical–subcortical lesions, located in both supratentorial cortex and subcortex; cerebellar lesions, confined to the cerebellum; brainstem lesions, confined to the brain stem and multiple lesions, lesions located in more than one of the above defined areas. This predefined protocol of DWI location has been utilized in prior studies 16,17

Group II, time window: patients were categorized into two different subgroups depending on whether they were admitted within or after 6 h of stroke onset.

Group III, persisting major occlusion or no occlusion: patients were categorized into two different subgroups according to the presence of total proximal middle cerebral artery (MCA) occlusion or no occlusion of any cerebral vessel on MRA at 24 h. Total occlusion of intracranial arteries was defined as 100% occlusion on MRA.

…”
Section: Methodsmentioning
confidence: 99%
“…It is not understood if the distribution and morphology of lesions are related to the stroke etiology and may be a clue for the rapid determination of the stroke subtype. Previously, several studies reported that some of the DWI-MRI lesion patterns are more frequently seen in some stroke subtypes (5,6). In this study, we investigated the association of early DWI-MRI lesion characteristics with the ischemic stroke subtypes.…”
Section: Introductionmentioning
confidence: 96%